Characterization of an iron-ruthenium interaction in a ferrocene diamide complex - Green, Aaron G.; Kiesz, Matthew D.; Oria, Jeremy V.; Elliott, Andrew G.; Buechler, Andrew K.; Hohenberger, Johannes; Meyer, Karsten; Zink, Jeffrey I.; Diaconescu, Paula L. (Inorganic Chemistry, 2013)
Reaction of [fc(NH)]RuCl(PPh ) (fc = 1,1′-ferrocenylene) with 2 equiv of KOBu led to the formation of a diamido ruthenium complex, [fc(NH)]Ru(PPh), whose solid-state molecular structure revealed a short Fe-Ru distance. A metal-to-metal charge transfer band was observed in the electronic absorption spectrum of [fc(NH) ]Ru(PPh). The Fe-Ru interaction was characterized by resonance Raman spectroscopy for the first time and also by H NMR, UV-vis, NIR, Mössbauer spectroscopy, and X-ray crystallography. Density functional theory (DFT) calculations including natural bond order analysis, Bader's atom in molecules method, and time-dependent DFT (TDDFT) provided further support that the iron-ruthenium bond is a weak donor-acceptor interaction with iron acting as the Lewis base. © 2013 American Chemical Society.